The Effect of Directed Reading Thinking Activity (DRTA) Strategy on Students' Reading Comprehension - Juita Sari Puspita Dewi; Annisa Astrid; Ridha Ilma (Linguists : Journal Of Linguistics and Language Teaching, 2023)
The study aimed to investigate the notable impact of the Directed Reading Thinking Activity (DRTA) approach on the students' reading comprehension. The study was carried out at MAN 2, Palembang. The present study employed a quasi-experimental design utilizing quantitative research methodology. The researchers employed the convenience sampling method to gather data. The data were obtained via a reading comprehension test administered to students in the two classes, experimental and control. The study's findings examining the impact of implementing DRTA before and after utilizing a paired sample t-test indicate that the calculated T value of 27.797 exceeds the t-table value of 3.030. Thus, implementing the DRTA approach enhanced the students' reading comprehension in the experimental group. An independent sample t-test was conducted to examine the outcomes of the disparity between individuals who utilized the Directed Reading-Thinking Activity (DRTA) and those who did not. The findings showed that notable disparities in reading comprehension existed among students who received instruction via DRTA and those who did not. The DRTA technique offers advantageous outcomes for students as it fosters active and critical reading practices. Students enrolled in reading courses that engage in prediction and active reading demonstrates a proactive approach to learning, effectively harnessing their cognitive abilities to acquire knowledge on unfamiliar subjects. Furthermore, DRTA mandates that students maintain a record of their understanding of the text while reading.